Contribution of edible indigenous woody plants as a coping strategy during drought periods in the southeast lowveld of Zimbabwe: a review - Chinomona, Ruth R.; Kupika, Olga L.; Gandiwa, Edson; Muboko, Never (Frontiers in Climate, 2024)
Climatic change related extreme events such as droughts negatively affect local communities in the semi-arid savanna ecosystems. This study mainly records and analyses local knowledge on the use of edible indigenous woody plant species by local communities during drought periods, as a coping strategy, in southeast lowveld of Zimbabwe. Secondary data on utilization of edible indigenous woody plants were gathered from literature sources focusing mainly on the southeast lowveld parts of Zimbabwe and covering the period 2000–2019. Quantitative ethnobotanical data analysis involved computing the frequency of citation (FC), relative frequency of citation (RFC) and family importance value (FIV) to determine the local significance of indigenous woody plant species. A total of 23 species from 12 families were recorded as being used during drought periods with key species including baobab (Adansonia digitata), bird plum (Tamarindus indica), corky-monkey orange (Strychnos cocculoides) and black monkey orange (Strychnos madagascariensis). Major use categories were food, medicine, and livestock feed. The study findings points to the need for embracing indigenous woody plants as a buffer against drought in semi-arid parts of the savanna. Future projects should focus on developing innovative strategies such as value addition and promoting sustainable use and restoration of non-wood forest products as part of livelihood diversification under drought situations.